Humanization of care in forensic mental health wards: a qualitative study - Sylvie Anna Sollied; Monica Evelyn Kvande (International Journal of Qualitative Studies on Health & Well-Being)
Purpose To explore nurses’ experiences related to humanizing care in high-security forensic units. Methods This study has a qualitative design. Data consist of texts from study involved nine interviews with nurses working in two forensic mental health wards in Norway. The text was interpreted and analysed using Lindseth and Nordberg’s phenomenological—hermeneutical method. Results Through an interpretation process, three themes emerged: “Openness and responsiveness to patients’ stories”; “Attention to patients’ individual needs”; and “Humanistic care in strict environments”. Conclusion Nurses’ presence and caring attitudes in everyday forensic psychiatric care activities provide insights into individual patients’ lived experiences, vulnerability, fragility and tolerance limit. The ability to see and listen to patients at the human level and meet and respect patients in human fellowships is essential for care humanization. Additionally, the nurses in our study highlighted the need for nurses to feel safe and closely collaborate within professional healthcare teams.